A critical analysis of Professor Andrew Tracey's contribution to African music pedagogy and the field of applied ethnomusicology - Moyo, Vuyelwa O'Lacy (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
The research presented in this thesis is based on my interest and experience in forms of African music, ethnomusicology, and studying mbira with Professor Emeritus Andrew Tracey. When I arrived in South Africa in 2019 to join Rhodes University's Applied Ethnomusicology programme, I chose to study the mbira with Tracey as the idea of learning more about Zimbabwe through music was important to the formation of my identity. Through the lens of embodied learning and a practice-based approach in this research, I evaluate how Tracey's numerous contributions to African music pedagogy have improved prospects for African music scholars and students in terms of contributing to the goals of applied ethnomusicology. The primary purpose of this thesis is to respond to the absence of serious scrutiny of existing pedagogical approaches to African music at universities across South Africa. The contribution this research makes will be valuable to African music programmes across the continent as well as to practitioners of African traditional instruments, such as the marimba, mbira, timbila xylophones, nyanga pan pipes, and valimba xylophones. The thesis comprises five chapters. The first presents an introduction to the research, and its goals, procedures and approaches, along with an outline of the subsequent chapters. Tracey's biography is covered in the second chapter. A consideration of the state of African music teaching in other African countries such as Ghana, Kenya, and Zimbabwe; the history of African music; and the state of African music pedagogy in tertiary institutions in South Africa constitutes the third chapter. Chapter 4 comprises an analysis of Tracey's articles and data gathered from interviews, as well as my personal reflections as Tracey's student. The final chapter presents a summary of the preceding chapters, the study's findings, and suggestions for further research. A multidisciplinary approach was used for this thesis. The results finds that Tracey's articles had six common themes which he wrote about and are a contribution to African music pedagogy. These themes are the history of instruments, the structure of the instrument, the learning/playing technique, structure of the instrument, transcription and dance steps.
Keywords: Tracey, Andrew T N; Ethnomusicology; Music Instruction and study -- Africa; Mbira -- Zimbabwe